What does it mean to be abused? Analyzing gender violence through data survey - Safranoff, Ana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2017)
From the analysis of a large victimization survey, the article explores the subjective definition of abuse, that is, what is interpreted by women as such. The results show that, by itself, physical violence is the modality largely recognized as abuse, while at the opposite extreme is the sexual violence, which, for most women, is not identified as abuse. The article concludes that the study of gender violence through survey data should consider not only the subjective view of the abuse but also the technique so as to capture all the different forms of violence (physical, psychological and sexual).